Primary Chemotherapy for Inoperable Ovarian, Fallopian Tube, or Primary Peritoneal Cancer With or Without Delayed Debulking Surgery. Issue 4 (1st May 2012) - Saha, Antonio; Varughese, Mohini; Gallagher, Chris J.; Orphanos, George; Wilson, Peter; Oram, David; Jeyarajah, Arjun; Reynolds, Karina; Shepherd, John; McCormack, Mary; Olaitan, Adeola; McDonald, Nicola; et al.
Abstract : Objective: To describe the outcome of primary chemotherapy for women with advanced-stage epithelial ovarian or primary peritoneal cancer and delayed surgery when optimal debulking surgery cannot be achieved at diagnosis. Methods: Between 1998 and 2006, we retrospectively reviewed the overall survival and examined prognostic markers in consecutive patients who were not suitable for initial radical surgery because of the extent of disease and/or poor performance status. They were treated with a policy of primary platinum-based chemotherapy, followed whenever possible in responding patients by debulking surgery. Results: A total of 171 patients received least one cycle of chemotherapy. Eighty-six patients proceeded to surgery and 53 (31% of 171 and 62% of 86) had optimal (<1 cm) residual disease. Eighty-five patients did not undergo surgery because they remained unfit or had not responded sufficiently to chemotherapy. The median overall survival was 18.7 months (95% confidence interval [CI], 16.5–24.2). The median OS in the surgical group for optimal and suboptimal surgery was 40.8 (95% CI, 32.5–50.0) and 22.5 (95% CI, 17.7–37.1) months ( P = 0.005). On multivariate analysis, interval surgery and optimal surgery were the only independent prognostic factors (hazard ratios, 0.45 and 0.43, respectively; P = 0.009). In the nonsurgical group, CA125 response was an independent prognostic factor (hazard ratio, 0.34; P = 0.001) with an OS of 21.7 months (95% CI, 14.0–35.4) in women with a normal CA125 after treatment compared with 6.7 (95% CI, 4.5–7.8) months. Conclusions: In one third of the women, the tumor was optimally debulked after primary chemotherapy and their median survival was 40.8 months. Suboptimal debulking surgery after primary chemotherapy did not result in a better survival than that achieved after a chemotherapy response alone, suggesting that surgery may be avoided when imaging after chemotherapy demonstrates residual disease that cannot be optimally debulked.